PCB CNC Machine - Jafar Yasin; Hussam Salameh (My University, 2012)
This project will include the design of and implementation of a CNC machine to make PCB (PrintedCircuit Board). The first portion of the project will include a history of CNC in general case. The secondpart of the project will include the analysis about design our machine. Next, we will explain mechanicalstage in detail with photos. Next, Will show the movement mechanism of our machine and what type ofmotor we use with driven circuit. At last, software stage to explain how we program our micro controllerby an appropriate algorithm.

This project will include the design of and implementation of a CNC machine to make PCB (PrintedCircuit Board). The first portion of the project will include a history of CNC in general case. The secondpart of the project will include the analysis about design our machine. Next, we will explain mechanicalstage in detail with photos. Next, Will show the movement mechanism of our machine and what type ofmotor we use with driven circuit. At last, software stage to explain how we program our micro controllerby an appropriate algorithm.
PCB CNC Machine